Cultura de paz y formación ciudadana como bases de la educación en Colombia (2020)
This article aims to establish the importance of peace culture and citizenship education within the task of peace education. The study consists of a narrative review developed from the Colombian context, using academic and institutional documents as a source of information. The analysis found that peace culture and citizenship education are crucial and inherent concepts of peace education, therefore, they acquire a dynamic of interdependence that becomes essential to promote in societies where violence has prevailed, as the case of Colombia.